A Tale of Three Cities - Eisman, Michael Max (The Biblical archaeologist, 1978)
A study of the urban development of Jerusalem, Athens, and Rome, the three great ancient cities which are the fountain-heads of western civilization. The response that each made to its own urban crisis determined its place in history forever.